2008
DOI: 10.1007/s10795-008-9052-8
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of green bean yield, water deficiency and productivity using spectral indexes during the growing season

Abstract: Field experiments were carried out in the 2004 and 2005 growing seasons on drip irrigated dwarf green beans (Phaseolus vulgaris, humilis). Soil water content (SWC), spectral reflectance and yield were monitored. Based on these data crop evapotranspiration (ETc), soil water deficit index (SWDI), water use efficiency (WUE) and four separate spectral indexes were calculated. In order to determine use opportunities of spectral indexes for estimation of yield, SWDI and WUE, some statistical analyzes were made. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…Normalised Water Index allows an estimation of the water status of the crop (Hanks, 1988). The plant water status is an important parameter as it gives information that can be used to select tolerant cultivar to drought stress in breeding (Köksal et al, 2008;Munjal and Dhanda, 2005). In fact, low values of NWI consistently provided the best relationships with grain yield (Prasad et al, 2007) and in agreement also with what observed in the present work (Figs.…”
Section: Morphological and Physiological Changesmentioning
confidence: 99%
“…Normalised Water Index allows an estimation of the water status of the crop (Hanks, 1988). The plant water status is an important parameter as it gives information that can be used to select tolerant cultivar to drought stress in breeding (Köksal et al, 2008;Munjal and Dhanda, 2005). In fact, low values of NWI consistently provided the best relationships with grain yield (Prasad et al, 2007) and in agreement also with what observed in the present work (Figs.…”
Section: Morphological and Physiological Changesmentioning
confidence: 99%
“…Linear relationship between ET and snap bean yield were indicated by several researches as Gençoğlan et al (2006), Köksal et al (2008), Sezen et al (2008) and Saleh et al (2018). Polynomial relationships between irrigation level and snap bean yield were also indicated by Bozkurt & Mansuroglu (2018).…”
Section: Figure 2 Relationships Between Irrigation Water Et and Yieldmentioning
confidence: 91%
“…Precision agriculture also increases crop productivity and farm profitability through improved management of farm inputs, leading to better environmental quality [Larson and Robert, 1991;Mulla, et al, 1996;Mulla et al, 2002;Tian, 2002;Zhang et al, 2002;Mukherjee et al, 2010]. Among all the inputs, water (management, frequency, amount, spatial distribution) plays the most critical role in most crops, as in the case of tomato that needs irrigation throughout the growing season, since water stress may lead to significant reduction in crop yield [Obreza et al, 1996;Pulupol et al, 1996;May and Gonzalerz, 1999;Köksal, 2008;Patanè et al 2011]. For this reason, quantitative and rapid methods for evaluating leaf water status are required for plant water stress management in tomato.…”
Section: Introductionmentioning
confidence: 99%